Teaching Skills - Reading - Bocán, Jakub (Univerzita Pardubice, 2012)
The thesis deals with developing reading skills in the English Language Teaching and evaluation of didactic aids.
Rozvíjení čtecích dovedností
Keywords: čtení; text; komunikativní kompetence; reading; text; communicative competence